Fast response temperature measurement and highly reproducible heating methods for 96-well plates. (June 2004) - Shellman, Yiqun G.; Ribble, Deborah; Yi, Ming; Pacheco, Theresa; Hensley, Mark; Finch, Dudley; Kreith, Frank; Mahajan, Roop L.; Norris, David A.
Hyperthermia, the procedure of exposing cells to a temperature between 42° and 49°C, has been shown to be a promising approach for cancer treatment. To understand the underlying mechanisms of hyperthermic killing of cancer cells, it is critical to have an accurate temperature measurement technique and a heating method with high reproducibility. To this end, we have developed a method using fine thermocouples with fast response time to measure the temperatures in multiple wells of a 96-well plate. The accuracy of temperature measurement was ±0.2°C. Such a capability allows a complete record of the time and temperature of the treatment procedure and helps define an accurate thermal dose. We have also compared several methods for heating 96-well plates and found that use of copper blocks in contact with the lower surface of the 96-well plate in an incubator provides a highly reproducible heating method. The common method of using water bath to heat cells in vitro resulted in a decrease of cell viability even at the control temperature of 37°C and a decrease in the reproducibility of certain biological assays. In summary, using these improved techniques, proposed thermal dose can be defined more precisely, and highly reproducible heating in vitro can be achieved.